Green Supply Chain Management and Firm Performance: Evidence from Ghana’s Food Production and Processing Industry - Appiah, Listowel Owusu; Odartey, Michael (International Journal of Business Strategy and Social Sciences, 2021)
Based on the Natural Resource Based View (NRBV), this study examines the relationship between Green Supply Chain Management practices and Firm performance in response to calls for empirical evidence from developing country contexts, and the need to consider the Triple Bottom Line approach to sustainability performance measurement. The study is conducted among Food production and processing firms in Ghana. A structured questionnaire was administered to a Senior Manager in each of the respective organizations. Based on data collected from 94 firms, this study uses OLS regression to examine the relationship between GSCM implantation and operational, environmental, social, and economic firm performance. The results indicate a positive relationship between GSCM implementation and all four firm performance dimensions. This suggests that it is in the best interest of managers to deploy resources towards the implementation of green initiatives, as there are potential gains to be made in the long run.